RASIONALITAS PENGGUNAAN ANTIMIKROBA RESERVE DI RUANG INTENSIVE CARE UNIT RUMAH SAKIT DI BALI PASCA PROGRAM PENGENDALIAN RESISTENSI ANTIMIKROBA - Erma Ariningsih, Ida Ayu Made; Hartayu, TB. Titien Siwi (Cendekia Journal of Pharmacy, 2025)
Antimicrobials are used to treat patient with infectious diseases. Inappropriate use oof antimicrobials can trigger bacteria that are resistant to antimicrobials. Reserve group of antimicrobials are antimicrobials which is reserved and are used for the treatment of patients with MDRO. In an effort to increase the rational use of antimicrobials, the government formed KPRA which us tasked with controlling the use of antimicrobials in hospitals, One of the private hospital in Bali has also formed KPRA since 2018. The use of antimicrobials in the ICU is quite high, but there is no data regarding antimicrobial control rate in the ICU, so it is important to analyze the use of antimicrobials in the ICU after KPRA. This study aims to determine the rationality of using reserve group antimicrobials in the ICU. This research is a descriptive analytical study, quasi-experimental design. Data was taken retrospectively from June 2017-May 2021. The study population was all hospital inpatient during the study period. The research subjects were all patients in the ICU. Data source from patient medical records and HIS. The sample size is the total that meets the criteria. Inclusion criteria were all patient in the ICU with reserve antimicrobials group in the period June 20017-May 2029 (pre-PPRA) and June 2019-May 2021 (post PPRA). Exclusion criteria were all patients in the ICU but the data was incomplete. Data analysis uses DDD calculations and the Gyssen method. The result showed that the DDD rate did not change significantly. The most widely used antimicrobials are Ceftriaxone 1G, Levofloxacin 500mg, Levofloxacin 750mg, and Meropenem 1G. The number of vials used for antimicrobials in the ICU decreased by 75.46%. Rational use of reserve group antimicrobials after PPRA implementation increased by 42.85%. The rationality of using reserve group antimicrobials in the ICU after PPRA increase.